Miniature pellet extruder concept for robotic 3D printing application - Dixit, Ankit; Kumar, Vikash (Institute of Advanced Engineering and Science, 2022)
Additive manufacturing more commonly known as 3D printing has been in the limelight of manufacturing research for a long. Many advances have been made in the past in elementary printing techniques, materials, and post-processing schemes. In this paper, a concept of a miniature pellet extruder is added at the end of the articulated robotic arm. The idea is to create a system that capable to print larger and more complex shapes of any parts with the help of a low payload capacity robotic arm and provide output as a single-piece structure. It also helps to print and handle objects with larger and more complex geometry with an optimized cycle time. Knowledge from this research work will also help to choose not only the right low payload capacity robotic arm, but also provides a logical approach for selecting a pellet extruder over a filament extruder.